Desk-rejection of manuscript: How to avoid it - Shah, Jay Narayan (Journal of Patan Academy of Health Sciences, 2020)
It is true that authors do not like their manuscripts being rejected early at the editorial level, and they even think that it is an arbitrary judgment by the editor. Editors and journals take this rather seriously. Desk-rejection (DR) is an important issue for all, authors and editors alike. It occurs even before the peer review of the submitted manuscript begins. Most authors experience DR sometime during their careers, though we are not aware of it until we encounter one, and may take it as a shock. Many a times, the journal editor rightly points out that a DR is mostly due to a ‘premature’ submission of a ‘half-cooked’ manuscript. It may not pass through in the very beginning due to abstract of poor construct, lack of clearly defined purpose of the paper, low standard of procedures undertaken, and insignificant principal findings, also referred to as the important 3Ps. Up to 80% of the submissions are not processed further and are rejected early on within a few days without an external review.